The Estimated Effect of Physicians' Advice for Smoking Cessation and Assumed Tobacco Retail Price Increase on Smoker's Intention to Quit in Shanghai, China: A Cross-Sectional Study - Ruiping Wang; Ruiping Wang; Xiangjin Gao; Yan Qiang; Qiong Yang; Xiaopan Li; Bin Li (Frontiers Media S.A., 2021)
Background: Tobacco consumption produces a heavy disease burden worldwide, and tobacco price increase, an advertisement for tobacco-induced harm, graphic warning labels on cigarette packages and advice of physicians for quitting are policies that have been proved as effective smoking cessation measures. But evidence on the estimated effect of advice of physicians for quitting and assumed tobacco retail price increase on smoking cessation intention among smokers is still limited in China.Methods: From January to April of 2021, we recruited 664 current smokers in Songjiang district of Shanghai by a multistage sampling design. We implemented a logistic regression analysis to calculate the odds ratio (OR) and 95% confidence interval (CI) to explore how smoking cessation intention would be influenced by the assumed tobacco retail price increase as well as advice of physicians for quitting, and used the paired tabulation method to identify the salient tobacco control measures among smokers as well.Results: A total of 664 current smokers included 548 males (82.53%), with an average smoking duration of 22.50 years (SD: 11.52 years). About 68.79 and 43.67% of current smokers reported smoking cessation intention due to advice of physicians for quitting and the assumed tobacco retail price increase, respectively. Logistic regression analysis indicated that female smokers (OR = 2.85 and 4.55), smokers with previous smoking cessation attempt (OR = 3.71 and 3.07), longer smoking duration (OR = 2.26 and 2.68), lower smoking intensity (OR = 1.82 and 1.69), and heavier tobacco burdens (OR = 1.67 and 2.22) had the higher intention of smoking cessation both due to advice of physicians for quitting and due to assumed tobacco price increase, respectively. Meanwhile, the advice of physicians for quitting was more effective and acceptable (over 80%) than the assumed tobacco price increase for inducing smokers to consider quitting in Shanghai.Conclusions: Smokers have a high intention of smoking cessation in Shanghai, and the advice of physicians for quitting is a potentially more salient tobacco control measure than the assumed tobacco retail price increase. Incorporating smoking duration, intensity, personal burden as well as noncommunicable disease (NCD) status of smokers into the implementation of tobacco control measures is beneficial for descending smoking prevalence.